(untitled) (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Infertility is a medical as well as a psychological problem of the couples who suffer from it. To serve them efficiently, their sociodemographic profile must be taken into consideration during work up, treatment and counseling. Objective: The objective of the study was to describe and analyze the sociodemographic profile of the infertile women attending Bangabandhu Sheikh Mujib Medical University. Method: Descriptive analysis of data collected and compiled by interviewing the couples attending Infertility outdoor of Bangabandhu Sheikh Mujib Medical University. Results: 64.64% of the women were in the age group 20-29 years. 64.13% of women had 10 or less than 10 years of education. 79.79% of women were housewives.69.69%) of women were from urban areas, with 59.06% from within Dhaka city. 35.35% of the women were from low and 37.37% of the women were from middle socioeconomic condition. One third of women presented with less than three years of infertility. The ratio of primary and secondary infertility is 2:1. Badly managed labour and delivery was the most common cause of secondary infertility. Conclusion: The findings of the study help us understand the needs and abilities of the infertile women presenting to us and decide the best possible strategies of treating and counseling them. J Shaheed Suhrawardy Med Coll, December 2015, Vol.7(2); 63-65